Empowering Growth: Innovative Guidance Techniques for Children with Special Needs: A Comprehensive Literature Review - Arauf, Muta Ali; Nurhayati, Novida (Interdisciplinary Journal of Social Science and Education (IJSSE), 2024)
The purpose of the research is to explore in depth the development of guidance techniques for children with special needs that are tailored to the needs of children. This research uses a literature review approach method which is an explanation of theories, findings and other research sources taken from references to become the basis for conducting research. The sources of the literature come from books, journals, related articles and from the internet related to the theme discussed by the author, namely the development of guidance techniques for children with special needs. From the collection of some literature, it can be concluded that students with disabilities have the right to develop optimally according to their potential. BK teachers need to collect detailed data about students with special needs who will be given services. Through accurate assessment, counseling teachers can explore guidance techniques according to the conditions and needs and difficulties of students.